Copper-catalysed synthesis of 3-hydroxyisoindolin-1-ones from benzylcyanide 2-iodobenzamides. Issue 5 (16th January 2020) - Kavala, Veerababurao; Wang, Chen-Yu; Wang, Cheng-Chuan; Patil, Prakash Bhimrao; Fang, ChiaChi; Kuo, Chun-Wei; Yao, Ching-Fa
Abstract : Copper-catalysed synthesis of 3-hydroxyisoindolin-1-ones from benzylcyanide 2-iodobenzamides were achieved in one-pot two-step sequential reaction. Abstract : An efficient one-pot two-step sequential reaction for the synthesis of biologically active 3-hydroxyisoindolin-1-one derivatives from 2-iodobenzamide derivatives and various substituted benzyl cyanides in the presence of CuCl and cesium carbonate in DMSO is reported. Furthermore, 3-hydroxyisoindolinone derivatives possessing bromo substituents were obtained from 2-iodobenzamide and 2-bromobenzyl cyanide substrates in two steps. Benzyl cyanide has been successfully used for the first time as a benzoyl synthon for the synthesis of 3-hydroxyisoindolin-1-ones. Interestingly, the mechanism of formation of 3-hydroxyisoindolin-1-ones is a novel pathway that involves carbon degradation followed by ring contraction.